Recent toe cap shoe applications and direction for future research: a review / Mohd Hidayat Ab Rahman - Ab Rahman, Mohd Hidayat (College of Built Environment, 2023)
Safety shoes are essential gear to keep employees safe in various situations. Safety shoes are designed to shield the foot from flying debris.